Podium to Publication: An Analysis of Papers Presented at the British Association of Paediatric Surgeons (BAPS) Congress (2009–19) - Goneidy, Ayman; Macdonald, Alexander; Davenport, Mark (Journal of pediatric surgery, 2025)
The British Association of Paediatric Surgeons (BAPS) annual congress is an opportunity to present clinical and scientific data that may influence future practice. The presentation of the Abstract is but the first step towards definitive publication in the medical literature. Our aim was to review what the success rate has been from previous congresses. Abstracts were reviewed for the 11-year-period 2009 to 2019. A MEDLINE search using keywords from title and authors’ names was used to identify subsequent publication. Comparison with a previous dataset [1] (1999-2008) was also carried out. Linear data were compared for trend using Mann-Whitney-U. P ≤ 0.05 was accepted as significant. Data were expressed as median (interquartile range). 1061 abstracts were presented orally with 555 (52.3%) subsequently published. The number per year was 90 (81–106) compared to 81 (74–79) in 1999–2008 (P = 0.25), although with a higher number actually published thereafter [45 (32–54)% vs. 30 (27–35)%; P = 0.0003)]. Publication occurred in a wide range of journals (n = 99), with most being in the Journal of Pediatric Surgery (n = 251), albeit with a smaller proportion (49% vs. 69% formerly, P < 0.05). Overall, UK institutions contributed 52.6% (n = 558) of abstracts with 240 (43%) of them subsequently published at 19 (17–29)/year. The proportion of UK presentations had increased from 43% formerly (P = 0.016). Most UK presentations originated from institutions within London [41% vs. 45% formerly, P = 0.04]. There was a wide range of abstracts from institutions from outside of the UK (n = 49) with 38 (26–51) abstracts accepted each year and of these 62.4% were subsequently published at 20 (15–36)/year. There has been an increase in abstracts accepted for presentation over the period, together with a higher proportion actually reaching publication. A strong international contribution was noted which has also been maintained. London remains the primary source of abstracts and publications from within the UK, although there was a higher proportion from other UK centres noted over this period. Reference [1] Macdonald AL, Parsons C, Davenport M. Outcome of abstracts presented at the British Association of Paediatric Surgeons congresses (1999–2008). J Pediatr Surg. 2012; 47: 386-90. doi: 10.1016/j.jpedsurg.2011.09.043.